2024
DOI: 10.1021/acs.jpcc.4c00941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligands on the Reactivity of the Undercoordinated Fragment Ions of Co6S8(PEt3–xPhx)6+ (x = 0–3) Clusters on Surfaces

Habib Gholipour-Ranjbar,
Lidya Sertse,
Dylan Forbes
et al.

Abstract: Atomically precise ligated clusters are of interest to a broad range of applications in which their reactivity is often controlled by removing one or more ligands. This process generates under-coordinated species known to be chemically and catalytically active. Despite the power of this approach, selective ligand removal from clusters in the condensed phase is challenging. In this study, we generated well-defined, undercoordinated clusters by selectively removing one ligand in the gas phase. We then examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…[21][22][23][24] The emergence of electrospray ionization (ESI), a so ionization technique that enables transferring of intact ions from solution into a mass spectrometer, has facilitated the deposition of a broad range of ions for the analysis of their structures and reactivities on substrates. [25][26][27][28][29][30][31][32] For example, scanning tunneling microscopy of cis-bis(isothiocyanato)bis(2,2 0bipyridyl-4,4 0 -dicarboxylato)-ruthenium(II) on a Au(III) surface revealed that its gas-phase geometry is distorted on the surface to maximize ligand-surface interactions. 33 In another study, so landed vanadium-benzene sandwich clusters were shown to orient on a CH 3 -terminated self-assembled monolayer on gold (HSAM) to maximize interactions between the aromatic rings of the cluster and methylene groups of the HSAM.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The emergence of electrospray ionization (ESI), a so ionization technique that enables transferring of intact ions from solution into a mass spectrometer, has facilitated the deposition of a broad range of ions for the analysis of their structures and reactivities on substrates. [25][26][27][28][29][30][31][32] For example, scanning tunneling microscopy of cis-bis(isothiocyanato)bis(2,2 0bipyridyl-4,4 0 -dicarboxylato)-ruthenium(II) on a Au(III) surface revealed that its gas-phase geometry is distorted on the surface to maximize ligand-surface interactions. 33 In another study, so landed vanadium-benzene sandwich clusters were shown to orient on a CH 3 -terminated self-assembled monolayer on gold (HSAM) to maximize interactions between the aromatic rings of the cluster and methylene groups of the HSAM.…”
Section: Introductionmentioning
confidence: 99%